Internet Resource Pricing Models - Xu, Ke. (SpringerBriefs in Computer Science,, 2014)
This brief guides the reader through three basic Internet resource pricing models using an Internet cost analysis. Addressing the evolution of service types, it presents several corresponding mechanisms which can ensure pricing implementation and resource allocation. The authors discuss utility optimization of network pricing methods in economics and underline two classes of pricing methods including system optimization and entities' strategic optimization. The brief closes with two examples of the newly proposed pricing strategy helping to solve the profit distribution problem brought by P2P free-riding and improve the pricing efficiency with the introduction of the price discrimination. The Internet resource pricing strategy is not only the key factor of Internet resource allocation efficiency, but also the determinant of the profit. The methods and models discussed in Internet Resource Pricing Models increase the efficiency of existing pricing strategies to ensure a sound and sustainable development of the Internet. The brief will help researchers and professionals working with this key factor of Internet resource allocation.